It is an algebraic expression that can be simplified to: 3x-11
It is an expression that can be simplified to: 3x-20
3x + 11 + 5*75 = 3x + 386. That is as far as the expression can be simplified.
Without an equality sign it is not an equation but the given expression can be simplified to: 2x+5
4x + 5 = 3x + 84x-3x + 5 - 5 = 3x - 3x + 8 -5x = 3
It is an algebraic expression that can be simplified to: 3x-11
It is an expression that can be simplified to: 3x-20
3x + 11 + 5*75 = 3x + 386. That is as far as the expression can be simplified.
It is: 3x+10y+5 simplified
3x - 8y + 2x - 5 - 5y = 5x -13y - 5
3x - 2 + 5 = 16 3x + 3 = 16 3x = 13 x = 13/3 ~ 4.333
-2x^4+16 +2x^4+9-3x^5=-3x^5+25. There is no "answer" because there is no equation.
20+6y is the equation simplified, but there is no way to figure out the answer.
-6 + 3x - y - 4x + 4y + 5 (combine like terms) = (-6 + 5) + (3x - 4x) + (-y + 4y) = -1 - x + 3yHope this helps :)
Without an equality sign it's not an equation but it can be simplified to: 7x-5
Removing brackets: 5x+5-2x+10 = 3x+15 simplified
Without an equality sign it is not an equation but the given expression can be simplified to: 2x+5